Optimalisasi Pengelolaan Bisnis untuk Kemajuan Ekonomi Lokal: Analisis SWOT pada Angkringan Asli Jogja, Kota Batu - Rahayu, Nika Esti; Ibrahim, Rosida; Primasiwi, Asri (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
This community service activity aims to analyze and provide strategic recommendations for optimizing MSME business management based on SWOT analysis. This community service was carried out on October 1-31, 2024 at Angkringan Asli Jogja, Batu City. The method used is discussion and mentoring with 6 stages of activities. This community service has resulted in the original Angkringan of Jogja having the potential for strengths in the form of an experienced and trained team, a varied and affordable menu and an efficient operational process. The weaknesses in this angkringan are the limited number of employees, product innovation that is still lacking, and financial management that is not optimal. Angkringan Asli Jogja has opportunities, namely increasing interest in local culinary and consumer trends that prioritize cheap food and culinary experiences. The threats that need to be considered for this angkringan are fierce competition in the culinary sector and rapid changes in consumer tastes. Based on the results of the satisfaction survey for this activity, it was obtained that 61% of the participants were very satisfied with the delivery of the material and the relevance of the strategic recommendations to the conditions of MSMEs, while 39% of the participants were satisfied with the Community Service activities carried out.